The Role of NF-ΚB Inhibitors in Cell Response to Radiation - Molavi Pordanjani, Sajjad; Jalal Hosseinimehr, Seyed (Current Medicinal Chemistry, 2016)
It is well documented that ionizing radiation (IR) activates the transcription factor (NF-κB) which is a trigger for resistance cancer cells to treatment. It is involved in activation of pro-survival signaling pathways and resulting in cancer development and progression. In unstimulated condition, NF-κB is sequestered in cytoplasm but after the cell exposure to IR, proteasomal degradation of IΚB flowing phosphorylation via IKK, leads to aberrantly NF-κB activation and nuclear translocation. Therefore, interruption in IΚB degradation, proteasome action, IKK phosphorylation and NF-κB nuclear translocation provide robust strategies for inhibiting adverse effect of IR induced NF-κB. In spite of uncompleted elucidation of NF-κB molecular mechanisms, different NF-κB inhibitors have been used in order to inhibiting the IR induced NF-κB. The aim of this review is to highlight the role of IR induced-NF-κB inhibitors such as MG132, bortezomib, curcumin, DHMEQ, naringin, sorafenib, genistein and parthenolide in suppression of IR induced NF-κB adverse effects. Moreover, their chemical, structural characteristics and molecular mechanisms will be discussed.
Keywords: radioprotective